The solar age - Plank, Natalie; Hodgkiss, Justin (New Zealand Science Review, 2015)
​It is appropriate that the International Year of Light will see us capture more of our energy needs from light than ever before. The global photovoltaic (PV) power capacity is estimated to rise to over 230,000 MW in 2015, a stunning growth of over 600 % since 2010 (Figure 1) to reach 4.4 % of total global electricity capacity. This surge in PV installations has outstripped all expec-tations (and revised expectations) from the International Energy Agency and even Greenpeace. Early PV growth was fuelled by aggressive subsidy programmes, particularly in Germany, that aimed to make this renewable energy source competitive with energy from fossil fuels. However, it is less widely known that price parity has already arrived, with solar PV beating existing energy sources directly on price in some parts of the world. This article will briefly review the rise of solar PV and provide a glimpse of new materials being developed for the next PV revolution, including research activities in New Zealand.